STUDI PENGARUH TATA LETAK STRUKTUR GABUNGAN GROIN I DAN L TERHADAP PEMBENTUKAN GARIS PANTAI - , Khusnul Setia Wardani, Prof. Ir. Nur Yuwono, Dip.HE., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Damage to the beach due to natural factor, such as, is due to wave attack, sea level rise, natural disasters, an imbalance of sediment supply, and tidal waves caused by storms. Human activities such as mining of sand and coral reefs, mangroves, and construction are not familiar environments also affect the condition of the beach. Interaction between coastal protection structure and dynamics of coastal and shoreline profiles need to be studied properly so it can be formulated in a stable condition coastal protection condition varies. New Innovations in coastal protection system using soft engineering has been growing in the world. One form of protection system in the form of an artificial sand beach. Since 2002 the use of artificial beaches nourishment as a coastal protection options are implemented in Indonesia. Composite structure groin I and L is a combination of groin and offshore breakwaters input parallel the coast. This research was conducted in a 3D physical model test. The study of hydraulic model test 3-D is to see the phenomenon of influence of composite structure groin I and L in maintaining the stability of the shoreline. Grain size of sediment d50 1.05 mm and initial slope coastline n = 6 is used in this study. The study also showed salient and tombolo formation as a new system of balance at the shoreline. Comparison between the Lx/L is used to analyse the relationship between the layout structure with the formation of a new equilibrium coastal. Layout of composite structure groin I and L toward wave length in equilibrium condition has achieved important results in the weak salient formation at Lx/L <0.81, pronounced Salient at 0.81 <1.1, and earlier tombolo at Lx/L > 1.1. The more steep waves, then the slope of the shoreline profile will be more sharply on the open zone and the ramps in the protected zone. This is due to the larger currents that occur, thus moving the sediment toward the shade. In the protected zone is obtained n1 = 13.917, n2 = 3.972, and n3 = 7.367, obtained the transition zone n1 = 7.704, n2 = 6.982, and n3 = 7.302 and obtained an open zone n1 = 4.025, n2 = 12.133, and n3 = 4.750. Bar formation occurs when n1 and n3 is less than n2. Berms formation occurs when n1 and n3 is greater than n2.